Dowód w matematyce — dziś i jutro - Murawski, Roman (Filozofia Nauki, 2013)
The paper is a review of the book by Krzysztof Wójtowicz, O pojęciu dowodu w matematyce [On the Concept of Proof in Mathematics]. It presents the main theses of the book and evaluates them.